Modelling Consumer Adoption of Internet Shopping - Kamarulzaman, Y. (IBIMA Publishing, 2008)
The study explores consumers’ adoption of Internet shopping in the context of tourism products in Britain. The key objective is to propose a model for the prediction of Internet shopping adoption integrating individual and technology characteristics. Drawing upon Davis’ (1989) Technology Acceptance Model (TAM), the proposed model identifies the structural relationships among eight constructs which were examined through Structural Equation Modelling (SEM) with AMOS. Essentially, this framework helps to explain issues such as reasons of adopting Internet shopping medium and contributing factors to Internet shopping adoption. The study employs an Internet Survey in the data collection stage. The method of analysis via SEM tested the hypothesised relationships among the constructs, as postulated in the model. The results explicitly clarified several key contributions and implications to marketing theory and practice.